Identification and cross-validation of autophagy-related genes in cardioembolic stroke - Yang, Yufang; Zhang, Min; Li, Ziqing; He, Shen; Ren, Xueqi; Wang, Linmei; Wang, Zhifei; Shu, Shi (Frontiers in Neurology, 2023)
Objective Cardioembolic stroke (CE stroke, also known as cardiogenic cerebral embolism, CCE) has the highest recurrence rate and fatality rate among all subtypes of ischemic stroke, the pathogenesis of which was unclear. Autophagy plays essential roles in the development of CE stroke. We aim to identify the potential autophagy-related molecular markers of CE stroke and uncover the potential therapeutic targets through bioinformatics analysis. Methods The mRNA expression profile dataset GSE58294 was obtained from GEO database. The potential autophagy-related differentially expressed (DE) genes of CE stroke were screened by R software. Protein-protein interactions (PPI), correlation analysis, gene-ontology (GO) enrichment analysis were applied for the autophagy-related DE genes. GSE66724, GSE41177 and GSE22255 were introduced for verification of the autophagy-related DE genes in CE stroke and the differences of values were re-calculated by Student t test. Results A total of 41 autophagy-related DE genes (37 up-regulated genes and 4 downregulated genes) were identified between 23 Cardioembolic Stroke patients(≤3 hours , prior to treatment) and 23 healthy controls. The KEGG and GO enrichment analysis of autophagy-related DE genes indicated several enriched terms related to autophagy, apoptosis and ER stress. The PPI results demonstrated the interactions between these autophagy-related genes. Moreover, several hub genes specially for CE stroke were identified and re-calculated by Student t test. Conclusion We identified 41 potential autophagy-related genes of CE stroke through bioinformatics analysis. SERPINA1, WDFY3, ERN1; RHEB and BCL2L1 were identified as the most significant DE genes which may affect the development of CE stroke by regulating autophagy. CXCR4 was identified as a hub gene of all types of strokes. ARNT, MAPK1, ATG12, ATG16L2, ATG2B, BECN1 were identified as particular hub genes for CE stroke. These results may provide an insight into the role of autophagy in CE stroke and contribute to the discovery of potential therapeutic targets for CE stroke treatment.